Identification of a Shrimp E3 Ubiquitin Ligase TRIM50-Like Involved in Restricting White Spot Syndrome Virus Proliferation by Its Mediated Autophagy and Ubiquitination - Zhao, Chao; Peng, Chao; Wang, Pengfei; Yan, Lulu; Fan, Sigang; Qiu, Lihua (Frontiers in Immunology, 2021)
Most tripartite motif (TRIM) family proteins are critical components of the autophagy machinery and play important roles in host defense against viral pathogens in mammals. However, the roles of TRIM proteins in autophagy and viral infection have not been studied in lower invertebrates, especially crustaceans. In this study, we first identified a TRIM50-like gene from Penaeus monodon (designated PmTRIM50-like), which, after a white spot syndrome virus (WSSV) challenge, was significantly upregulated at the mRNA and protein levels in the intestine and hemocytes. Knockdown of PmTRIM50-like led to an increase in the WSSV quantity in shrimp, while its overexpression led to a decrease compared with the controls. Autophagy can be induced by WSSV or rapamycin challenge and has been shown to play a positive role in restricting WSSV replication in P. monodon. The mRNA and protein expression levels of PmTRIM50-like significantly increased with the enhancement of rapamycin-induced autophagy. The autophagy activity induced by WSSV or rapamycin challenge could be inhibited by silencing PmTRIM50-like in shrimp. Further studies showed that rapamycin failed to induce autophagy or inhibit WSSV replication after knockdown of PmTRIM50-like. Moreover, pull-down and in vitro ubiquitination assays demonstrated that PmTRIM50-like could interact with WSSV envelope proteins and target them for ubiquitination in vitro. Collectively, this study demonstrated that PmTRIM50-like is required for autophagy and is involved in restricting the proliferation of WSSV through its ubiquitination. This is the first study to report the role of a TRIM family protein in virus infection and host autophagy in crustaceans.